Adaptive shading for energy retrofitting: a case study of high-rise residential buildings in Saudi Arabia - Zameem, Mahmoud Ibrahim (2024)
This thesis investigates the energy retrofitting (ER) of buildings within the Kingdom of Saudi Arabia (KSA), a sector significantly influencing the country's energy consumption. The research develops an approach adapted to the local climatic conditions, intending to enhance energy efficiency, comfort, and align with Saudi Arabia's 2030 objective. Utilising a case study framework, the methodology integrates a self-actuating Shape Memory Polymer (SMP) material into a shading system to dynamically respond to fluctuating weather conditions, assessing its impact on the thermal and energy performance of existing high-rise apartments, identifying appropriate energy retrofitting measures. Investigating cutting-edge energy retrofitting technology, the research integrates smart materials into shading systems , facilitating movement and precise control, leveraging the sun's renewable energy as the activation source. The SMP material plays a crucial role in a self-actuating shading system, dynamically responding and adapting to changes in weather. System performance is validated through a comparative analysis with an existing high-rise apartment, showcasing effectiveness in minimising heat gain, indoor temperature, and enhancing thermal comfort, leading to substantial energy savings and decreased carbon emissions by reducing cooling loads. The thesis emphasises the importance of government decision-makers actively supporting and providing incentives for energy retrofitting, recognising its various benefits. The proposed approach offers a pathway for stakeholders to transition toward a more energy-efficient, economically viable, and environmentally responsible building sector in KSA. These technology-based guidelines on energy retrofitting provide practical insights for individuals governments, designers, and industry specialists aiming to improve energy efficiency and promote sustainable development.